Cover Picture. Issue 3 (9th September 2019) - Colón‐Santos, Stephanie; Cooper, Geoffrey J. T.; Cronin, Leroy
Abstract : The Front Cover shows the complexity of the combinatorial explosion in the formose reaction and formamide condensation, becoming refined into distinct products through cycles and the influence of minerals. More information can be found in theCommunication by S. Colón‐Santos et al .